Tingkat Motivasi Belajar Siswa Kelas X dalam Pembelajaran PJOK SMK Negeri 1 Cerme Gresik - Ardiansa Mohtar; Andhega Wijaya (Journal on Education, 2024)
The aim of this research is to determine the level of motivation among 160 grade 10 students at SMK Negeri 1 Cerme Gresik during the 2023/2024 academic year when taking sports and health education, especially on the 5th and 6th days from 10.15 to 11.45. This descriptive study used a survey questionnaire for data collection, and all 10th grade students who attended physical education and health at the specified time were included in this study. The reliability test produces a value of 0.978, while the validity is marked with a value of 0.950. The results of calculations through quantitative descriptive analysis found the distribution of motivation scores - very large at 6% or 9 students, large at 23% or 37 students, medium at 38% or 60 students, low at 26% or 41 students, and very little at 8% or 13 students. From this, it can be seen that the level of motivation among the participants is quite high. These findings can help educators understand their students' motivation and provide insight for both students and staff in improving the factors that drive success.